PENGARUH DOSIS PUPUK KASCING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PAKCOY (Brassica rapa L.) - Ano, Bertoldus; Bagus Putu, Udiyana; I Dewa Nyoman, Raka (Agrofarm: Jurnal Agroteknologi, 2023)
One of the several vegetables that can be cultivated with an organic system is the pakcoy mustard plant. Pakcoy mustard is a type of vegetable that many Indonesians like because it tastes good and contains lots of vitamin A and vitamins C. In addition, the pakcoy plant has a high nutritional content, not inferior to other vegetable crops. Vermicompost fertilizer is organic material produced by worm droppings mixed with soil and other organic matter. Vermicompost is a fairly good organic material because it can improve the physical, chemical and biological properties of soil, especially in infertile soils such as ultisol type soils, it also does not have a negative effect on the environment in wet sub-tropical areas where the weathering process is advanced. The purpose of this study was to determine the best dose of vermicompost fertilizer on the growth and yield of mustard greens (Brassica rapa L.). This study used a randomized block design (RBD) method with six treatments, namely treatment without a dose of vermicompost fertilizer (P0), a dose of vermicompost fertilizer 2 tons/ha (10 g/10 kg soil/polybag) P1, a dose of vermicompost fertilizer 4 tonnes (20 g/10 kg of soil/polybag P2, the dose of vermicompost fertilizer is 6 tonnes/ha (30 g/10 kg of soil/polybag) P3, the dose of vermicompost fertilizer is 8 tons (40 g/10 kg of soil/polybag P4, and the dose 10 tons of castor fertilizer (50 g/10 kg of soil/polybag) P5. Each treatment was repeated four times so that the total number of treatments was 24. Based on data analysis, the treatment with vermicompost doses had a very significant effect on plant height (cm), number of leaves (strands ), leaf area (cm2), total fresh weight planted (g), and total oven dry weight of plants (g).Giving a dose of vermicompost fertilizer 4 tons/ha (P2) on mustard greens gave the best growth and yield on total fresh weight plant (184.25 g) and total plant oven dry weight (22.55 g).